The Role of Public Relations in Spreading the Culture of Competition and Combating Monopolistic Practices at the General Authority for Competition: A Survey Study (The International Journal of Educational Sciences and Arts, 2024)
This research aims to study the role of the General Authority for Competition in promoting a culture of competition and combating monopolistic practices in the Saudi market, as well as the role of public relations in raising public awareness of these laws and practices. Data were collected through a questionnaire directed to 200 participants, where demographic data were analyzed and participants' opinions were identified about the means of communication used by the Authority, the awareness activities it carries out, the role of public relations, in addition to the topics covered in communication activities and proposals for developing public relations strategies. The results showed that most of the participants were males, with a variety of age groups, and most of them enjoyed a high level of education, and they worked in the public and private sectors. Regarding means of communication, it was found that the General Authority for Competition effectively uses traditional media and social media to spread awareness of competition and anti-monopoly laws. Digital advertising was also used as a main tool to promote a culture of competition. As for awareness activities, the data showed that the Authority organizes awareness events, participates in exhibitions and forums to highlight the risks of monopoly, and holds educational workshops for institutions and companies. The role of public relations in raising public awareness through social media and electronic means was highly appreciated by the participants, reflecting the importance of these channels in activating interaction with the public. Regarding proposals for developing strategies, participants suggested using modern technology such as artificial intelligence and improving electronic applications to increase public awareness of competition, in addition to enhancing cooperation with academic institutions and organizing virtual seminars. The study recommends the need to enhance the use of technology and improve public relations strategies to increase the effectiveness of awareness of competition laws, while expanding partnerships and developing innovative media content.
Keywords: The Role of public relations; Spreading the culture of competition; Combating monopolistic practices; the General Authority for Competition; Legal awareness; Media; social media; Awareness strategies